Assessing Reading Comprehension Skills in Student Teachers - Ríos Higuera, Selenne (2019)
Education majors training to become high school teachers must possess good reading comprehension skills. It is, therefore, necessary to be able to gauge this skill among future teachers. This objective of this study was to test current reading comprehension skills among a group of student teachers through a test involving a text about the importance of Media in teaching, followed by twelve comprehension questions. The questions explored three areas of reading comprehension: 1) literal, 2) inferential and 3) analogical. The sample group included 56 Education Majors specializing in High School English and Mathematics at the Escuela Normal Superior in Northwest Mexico. Based on the data collected, students had the most difficulties with literal and critical questions.  The importance of this study is that it helps identify challenges faced by undergraduate students in this area at this institution and emphasizes the need to foster the development of reading comprehension skills.